Devising directions for unifying innovation flow in Ukraine in the context of its European integration, given the conditions of the ongoing armed conflict and the prospects of post-war reconstruction - Davydiuk, Oleksandr; Shovkoplias, Hanna; Malovatskyi, Oleksii; Ivanova, Hanna; Tsiupak, Volodymyr (Eastern-European Journal of Enterprise Technologies, 2025)
This study considers the system of normative, regulatory, managerial techniques and procedures for identifying innovations in Ukraine and the European Union, as well as their comparison. The study aims to address the unification of innovation flow in Ukraine with the requirements from the European Union. The directions, techniques, and procedures to unify normative regulation of innovation flow in Ukraine with the law of the European Union have been examined. The study of the processes that regulate innovation flow in Ukraine and the European Union has established their inconsistency with each other. It was determined that such inconsistency stems from the heterogeneity of approaches to identifying innovations in the European Union. It has been proven that the unification of regulation of innovation flow in Ukraine with the requirements of the EU should be holistic and systemic. The following directions to unify innovation regulation in Ukraine have been substantiated: complex, object-based, network, concentration. The need for unification of Ukraine's regulatory rules with the recommendations of WIPO, the TRIPS Agreement, the Oslo Guidelines, the Horizon Europe Framework Agreement, the European Innovation Act, etc. was proven. The need for amendments to the provisions of the Law of Ukraine "On Innovation Activity" was substantiated. The study is aimed at forming general theoretical principles for improving the regulation of innovation flow in Ukraine. The results could be used to improve the official rules for the dissemination and circulation of innovations, the formation of relevant decisions of state authorities, state innovation policy, and the basis for further scientific research on the specified issues. The conclusions from this study could be used to resolve problematic issues of unification of the current legislation of Ukraine with the requirements of the European Union, as well as with international agreements and documents